PENINGKATAN KEMAMPUAN BERPIKIR KRITIS SISWA PADA MATA PELAJARAN IPAS MENGGUNAKAN MODEL PEMBELAJARAN INKUIRI - Cindy Septina; Rizki Ananda; Putri Hana Pebriana; M. Syahrul Rizal; Joni (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This research is motivated by the low critical thinking skills of students in the subject of science in class IV of UPT SD Negeri 001 Bangkinang City. One solution to overcome this problem is to apply the inquiry learning model. The purpose of this study is to describe the improvement of students' critical thinking skills through the inquiry model in class IV of UPT SD Negeri 001 Bangkinang City. The method in this study is Classroom Action Research (CAR) which is carried out for two cycles. Each cycle consists of two meetings and four stages, namely, planning, implementation, observation, reflection. The time of this research was carried out at the end of May and early June 2025. The subjects of this study were 10 class IV students consisting of 2 boys and 8 girls. The data collection instruments in this study were observation sheets, test sheets, documentation. Based on the results of the study, it can be concluded that the critical thinking skills of class IV students of UPT SD Negeri 001 Bangkinang City through the pre-action test were 20%, cycle I meeting I was still the same, namely 20%. In cycle I meeting II it increased to 40%. Furthermore, in cycle II, meeting I became 60% and increased in meeting II to 80%. The conclusion is that using the inquiry model can improve students' critical thinking skills in the Science subject in class IV of UPT SD Negeri 001 Bangkinang City.